The Review on Eye-Tracking Studies in L2 Assessment - Xi, Cao; Zhenni, Ma (Colombian Applied Linguistics Journal, 2025)
The use of eye-tracking methodology in L2 assessments has become increasingly common, focusing on examining the cognitive validity of tests and the processing patterns of test takers. This paper reviews both empirical and theoretical studies on eye-tracking in L2 assessments and its applications in language education research. Through the lens of cognitive psychology, the paper examines the fundamental principles and primary applications of eye-tracking in L2 assessment. It also discusses potential theoretical and pedagogical implications. Finally, it highlights the limitations of current studies in this field and offers suggestions for future research to broaden the scope of eye- tracking studies in language testing and assessment.